Using artificial intelligence-based chatbots for interactive Ukrainian language learning - Strohanova, Hanna; Stepanenko, Olena; Popovych, Anzhelika; Krymets, Oksana; Udovychenko, Larysa (My University, 2025)
The use of chatbots based on artificial intelligence (AI) for teaching the Ukrainian language was considered highly relevant in the context of the digitalization of education and the increasing demand to make students’ speech development more effective. Interactive tools were found to engage students more actively in the learning process, addressing the limitations of traditional methods that often failed to accommodate individual learners’ needs. The aim of the study was to evaluate the impact of AI-based chatbots on the development of speech competencies among secondary school students. The methodology included a questionnaire survey of students, a pedagogical experiment involving chatbot-assisted learning, comparative analysis of learning outcomes between the control group (CG) and the experimental group (EG), and systematic observation of speaking activity. The study confirmed that the use of chatbots significantly improved students’ speaking skills, increased their motivation, and enhanced lesson interactivity. Specifically, the EG students demonstrated a 27% improvement in productive speech performance and a 35% increase in the number of speech acts. In comparison, the CG showed only a 12% increase in productivity and a 9% rise in speech acts, which was notably lower than the EG results. The conclusions highlighted that the integration of chatbots contributed to the development of sustainable communicative skills and supported students’ motivation to learn. Teachers acknowledged the pedagogical potential of such tools but also emphasized the need for additional training and improved technical infrastructure. The academic novelty of the research lay in the development of an interactive methodology for teaching Ukrainian, which effectively combined traditional practices with innovative approaches such as personalization and gamification. The practical value consisted in the applicability of the results for improving Ukrainian language instruction, guiding the integration of AI tools into curricula, and enhancing teacher qualifications.
Keywords: language competence; adaptive methods; innovative approaches; educational progress; educational interactivity; digital pedagogy; chatbots; Ukrainian language